Tallinn manual on the international law applicable to cyber warfare - Schmitt, Michael N. (Cambridge University Press, 2013)
The result of a three-year project involving twenty international legal experts, this manual sets forth the international law applicable to cyber warfare, whether engaged in by States or non-State actors.